2013
DOI: 10.1016/j.cell.2013.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Control of Blood Progenitor Maintenance

Abstract: SUMMARY Drosophila hematopoietic progenitor maintenance involves both near neighbor and systemic interactions. This study shows that olfactory receptor neurons (ORNs) function upstream of a small set of neurosecretory cells that express GABA. Upon olfactory stimulation, GABA from these neurosecretory cells is secreted into the circulating hemolymph and binds to metabotropic GABAB receptors expressed on blood progenitors within the hematopoietic organ, the lymph gland. The resulting GABA signal causes high cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
171
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(184 citation statements)
references
References 68 publications
5
171
0
Order By: Relevance
“…Thus, ARF1 negatively regulates differentiation and we found that this is due to its effect on the hematopoietic stem cell niche (PSC). Recent studies showed that lymph gland hematopoiesis is regulated by autonomous as well as systemic factors (26,27). Our analysis shows an essential resident role for ARF1 in the niche as well as for communication from the nonlymph-gland hemocytes.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, ARF1 negatively regulates differentiation and we found that this is due to its effect on the hematopoietic stem cell niche (PSC). Recent studies showed that lymph gland hematopoiesis is regulated by autonomous as well as systemic factors (26,27). Our analysis shows an essential resident role for ARF1 in the niche as well as for communication from the nonlymph-gland hemocytes.…”
Section: Discussionmentioning
confidence: 53%
“…Of note, however, the PSC is not orchestrating the LG response to all systemic inputs. For instance, food deprivation or odors have been found to directly impinge on prohemocyte fate (17,31). All together, these findings underscore the regulatory role of the PSC, which acts as a signaling hub to fine-tune hematopoiesis but whose presence is not essential for LG homeostasis under laboratory breeding conditions.…”
Section: Discussionmentioning
confidence: 93%
“…17 Briefly, the immunoassay was performed after extraction and derivatization of GABA from experimental samples. The antigen was bound to the solid phase of the microtiter plate.…”
Section: Detection Of Gaba By Elisamentioning
confidence: 99%